How did you specify your test suite. - Holzer, A; Schallhart, C; Tautschnig, M; Veith, H (ACM, 2010)
Although testing is central to debugging and software certification, there is no adequate language to specify test suites over source code. Such a language should be simple and concise in daily use, feature a precise semantics, and of course, it has to facilitate suitable engines to compute test suites and assess the coverage achieved by a test suite. This paper introduces the language FQL designed to fit these purposes. We achieve the necessary expressive power by a natural extension of regular expressions which matches test suites rather than individual executions. To evaluate the language, we show for a list of informal requirements how to express them in FQL. Moreover, we present a test case generation engine for C programs and perform practical experiments with the sample specifications. © 2010 ACM.